2013
DOI: 10.1002/14651858.cd007594.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyethyl starch (HES) versus other fluid therapies: effects on kidney function

Abstract: The current evidence suggests that all HES products increase the risk in AKI and RRT in all patient populations and a safe volume of any HES solution has yet to be determined. In most clinical situations it is likely that these risks outweigh any benefits, and alternate volume replacement therapies should be used in place of HES products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
130
0
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(149 citation statements)
references
References 92 publications
6
130
0
7
Order By: Relevance
“…(Grade 2+) STRONG agreement Rationale: Several randomized or observational studies and meta-analyses have examined the beneficial effect of a preferential administration of colloids compared to crystalloids [62][63][64][65][66][67][68][69][70][71][72][73]. In the ICU, the use of HES, regardless of its type, has been reported to be associated with an increase in mortality rate, AKI incidence and the need for RRT in several meta-analyses with a high level of proof [58][59][60][61][62][63][64][65][66][67][68][69][70][71]73]. A Cochrane meta-analysis simultaneously considering all colloids did not find any beneficial effect associated with the preferential use of colloids, regardless of nature, compared with crystalloids.…”
Section: How To Assess the Risk Of Akimentioning
confidence: 99%
“…(Grade 2+) STRONG agreement Rationale: Several randomized or observational studies and meta-analyses have examined the beneficial effect of a preferential administration of colloids compared to crystalloids [62][63][64][65][66][67][68][69][70][71][72][73]. In the ICU, the use of HES, regardless of its type, has been reported to be associated with an increase in mortality rate, AKI incidence and the need for RRT in several meta-analyses with a high level of proof [58][59][60][61][62][63][64][65][66][67][68][69][70][71]73]. A Cochrane meta-analysis simultaneously considering all colloids did not find any beneficial effect associated with the preferential use of colloids, regardless of nature, compared with crystalloids.…”
Section: How To Assess the Risk Of Akimentioning
confidence: 99%
“…Effect of HES fluid administration on therapeutic doses was no different from effect of crystalloid fluid on changes in serum creatinine levels. Nevertheless, mean creatinine serum level in crystalloid group and HES 200/0.5 group increased significantly Meta-analysis conducted by Mutter et al (2013) concluded differently. HES has the potential to increase the risk of acute kidney damage.…”
Section: Discussionmentioning
confidence: 90%
“…In particular hydroxyl ethyl starch (HES) has been associated with osmotic nephrosis and is best avoided [18]. Among the crystalloids buffered solutions such as Ringer's lactate may have benefits over isotonic saline [19].…”
Section: Prevention and Management Of Sepsis Induced Aki A) Fluid Resmentioning
confidence: 99%